KINETIKA PERUBAHAN KUALITAS FISIK PISANG KEPOK (Musa acuminata) DIBAWAH PENGARUH VARIASI LAMA WAKTU PEMAPARAN OZON DAN SUHU RUANG PENYIMPANAN - Dimas Triardianto; Nursigit Bintoro (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
As a climacteric fruit, bananas continue to ripen after being harvested and it’s accelerated by ethylene produced by the product. Post-harvest handling is needed to slow changes in the physical quality parameters of bananas for longer shelf life. Variation ozone gas exposure and storage room temperature are a potential methods to extend the shelf-life of bananas. The purpose of this study was to build a mathematical model of stored kepok bananas with variations in the duration of ozone gas exposure and storage room temperature. Green mature kepok bananas were used as the sample. The duration time of ozone exposure treatments used were 0 (untreated), 10, 15, and 20 minutes every day with a flow rate of 0.0279 ppm/menit. While the storage temperatures used were 5, 15, and 27oC (ambient temperature). Mathematical models are used to predict change rate (k) in the product quality during storage and predict the value of physical quality parameters (firmness, brix, pH, weight loss, and moisture content). The results of the change rate of quality of physical parameters show that the lower storage temperature and the longer of ozone gas exposure cause the rate change in the quality of the physical parameters to be lower. Meanwhile, the results of the model validation using the correlation coefficient (R2) and the P-value on chi-square (X2) show that mathematical models are well developed in predicting the value of physical quality parameters.